THE IMPACT OF SYRIANS UNDER TEMPORARY PROTECTION STATUS ON THE TURKISH ECONOMY (Third Sector Social Economic Review, 2022)
Türkiye started to see an influx of asylum seekers after civil war broke out in Syria in 2011 and the corridor between the two countries soon became one of the busiest migration routes in the world, as well as in Turkish history. As of 2022, Türkiye is host to more than 3.6 million “Syrians under Temporary Protection (SuTPs)”, who today account for approximately 4.5% of the total population of the country, similar to that of the fourth largest metropolitan city. While there have been many voluntary returns, factors such as the uncertainty of the solution to the crisis in Syria have led many SuTPs to prolong their stay and to make Türkiye their home, and records of childbirth in Türkiye reveal that SuTPs are set to be a permanent feature in the country. SuTPs are thus of great importance for Türkiye in terms of current and future political agenda and policy implementation. The present study examines the effects of SuTPs on the Turkish economy, beginning with a conceptual discussion of the causes and economic effects of migration. In the following section, the policies implemented by Türkiye will be examined along with the density, living areas, demographic characteristics and business lines of SuTPs. Finally, the economic impact of SuTPs and the simultaneously positive and negative consequences of their qualifications for Türkiye will be analyzed.
Keywords: Forced Migration; Syrians Under Temporary Protection; Work Permit; Skill Transfer